The Position and Nature of the Philosophy of Science in the Development of Scientific Knowledge - An An Siti Nurhasanah; Maspuroh; Najib Abdul Muta’al; Santi Rahmawati; Silvya Syariatul Qodariyah Jamal (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Philosophy of science is part of epistemology (philosophy of knowledge) which specifically examines the nature of science (scientific knowledge). Science is a branch of knowledge that has certain characteristics. Philosophy of science is a philosophical study that wants to answer several questions regarding the nature of science, such as, what objects does science study? What is the true nature of the object? What is the relationship between objects and human understanding (such as thinking, feeling and sensing) which produces knowledge. The aim of this research is to know, understand and comprehend the meaning, aims, essence, approach, way of working, foundation, objects, values ​​and uses of philosophy of science. This research uses a qualitative method, namely a descriptive and analytical research method. The results of this research are that philosophy of science is the study of all phenomena of human life and thought critically and described in fundamental concepts. Philosophy of Science is really needed in proving that accidents and phenomena and substances are proven to exist or are possible, because with reason you can prove a substance and that substance is formed from philosophy.